Determinantes del precio mundial del cobre periodo 1970 - 2017 - Paredes Aguilar, Liz Katherin (2019)
This research paper seeks to identify the main determinants of the world price of copper, from 1970 to 2017. In this research, annual world copper price data, world refined copper inventory, world copper production, average copper cathode cost, copper consumption in China, copper consumption in the rest of the world were used, average exchange rate of the US dollar and the world price of aluminum. These data were extracted from the Chilean Copper Commission, which proceeded to develop a logarithmic econometric model to determine and measure the degree of relationship that exists between the study variables. According to the results obtained in this research, it is concluded that the world inventory of refined copper and world copper production, the net cost of copper cathode, world price of aluminum and copper consumption in China and in the rest of the world, they are determinants of the world price of copper.